2011
DOI: 10.1039/c0cc03971c
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartmentalized polymersomes for selective encapsulation of biomacromolecules

Abstract: Multicompartmentalized polymersomes are formed using block co-polymers PMOXA-PDMS-PMOXA and PS-PIAT, and are subsequently proven to be capable of selective encapsulation of biomacromolecules. This architecture mimics the compartmentalization found in cells and may serve as a simple, albeit robust, model system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 29 publications
0
81
0
Order By: Relevance
“…2023 None of these well-established polymersome formulations, however, generates fully biodegradable vesicles via aqueous self-assembly. A few biodegradable polymersome compositions have been prepared from amphiphilic diblock copolymers of PEO and aliphatic polyesters/polycarbonates using an organic co-solvent/water injection/extraction method.…”
Section: Introductionmentioning
confidence: 99%
“…2023 None of these well-established polymersome formulations, however, generates fully biodegradable vesicles via aqueous self-assembly. A few biodegradable polymersome compositions have been prepared from amphiphilic diblock copolymers of PEO and aliphatic polyesters/polycarbonates using an organic co-solvent/water injection/extraction method.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent approaches consisted in forming the larger polymersomes by solvent-displacement method (or nanoprecipitation) with a suspension of smaller polymersomes previously formed by film rehydration as a water phase. [14] The drawback of this technique lies essentially in the poor encapsulation yield during nanoprecipitation. To overcome this limitation, other options, such as emulsions or double-emulsion techniques, have been investigated.…”
mentioning
confidence: 99%
“…So far, polymersomes have encapsulated a variety of proteins, including aquaporin Z (Kumar et al, 2007), cytochrome C (CC) (Hvasanov et al, 2011), hemoglobin (Rameez et al, 2008; Li et al, 2012), insulin (Xiong et al, 2007; Christian et al, 2009; Kim H. et al, 2012), immunoglobulin G (Fu et al, 2011), ovalbumin (Stano et al, 2013), and myoglobin (Kishimura et al, 2007). Recent investigations also have found that polymer vesicles with asymmetrical membranes exhibit much higher loading capacity of proteins than symmetrical polymersomes.…”
Section: Applications Of Asymmetric Polymersomesmentioning
confidence: 99%